1979
DOI: 10.1007/bf01968127
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the delayed hypersensitivity reaction to methylated bovine serum albumin in the mouse and its use in the evaluation of drug effects on cell mediated immune reactions

Abstract: On the basis of these studies a protocol for conducting the DH reaction to MBSA was established and the activity of drugs on processes underlying the sensitization phase of the reaction or processes underlying the elieitation phase of the reaction have been examined. Steroid and immunosuppressant drugs were found to inhibit the DH footpad response when dosed during the sensitization whereas several 'specific-antl-rheumatlc' and 'immunoactlve' compounds were without effect, lndomethacin and sudoxi cam inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Delayed hypersensitivity tests were not performed in these mice since such tests may have affected the progression of the arthritis. However, other workers have shown that prednisolone and dexamethasone can inhibit the elicitation of delayed hypersensitivity responses to Met-BSA in mice [25,26]. In these instances, higher doses of the steroids were administered over a much shorter period of time (4 days) making comparison with the mouse arthritis results difficult.…”
Section: Discussionmentioning
confidence: 98%
“…Delayed hypersensitivity tests were not performed in these mice since such tests may have affected the progression of the arthritis. However, other workers have shown that prednisolone and dexamethasone can inhibit the elicitation of delayed hypersensitivity responses to Met-BSA in mice [25,26]. In these instances, higher doses of the steroids were administered over a much shorter period of time (4 days) making comparison with the mouse arthritis results difficult.…”
Section: Discussionmentioning
confidence: 98%
“…For ex ample, the induction of arthritis by injecting MeBSA into knee joints in mice indicated that methylation of BSA induced cell-mediated responses rather than hu moral responses [7]. Footpad reactions [8] and skin reactions in mice [6], and an air pouch type inflamma tion in rats [25] also showed predominantly cell-medi ated responses. The weaker anaphylactic responses induced by MeBSA in comparison with those induced by ABA-AcBSA (table 1) might be related to weaker induction of humoral responses by the cationic pro tein MeBSA, since the anaphylactic responses are shown to be induced by IgE-mediated degranulation of mast cells [16,26],…”
Section: Discussionmentioning
confidence: 99%
“…For example, the protein de rived from Ascaris dominantly induces humoral, espe cially IgE-mediated allergic responses and is usually used for analysis of the immediate phase of allergic inflammation including asthmatic reactions [1,2], On the other hand, cationic proteins arc known to be suitable antigens for the induction of glomerulo nephritis and allergic arthritis in animal experiments [3][4][5], Methylated bovine serum albumin (MeBSA), a chemically modified cationic protein, predominantly induces cell-mediated responses [6][7][8][9], Thus the unique properties of cationic proteins as antigens arc explained by the observations that cationization of proteins changes the immunogenicity of native pro tein and increases the retention of the protein at in flammatory sites [3,10], However, there are few reports studying the acute phase of allergic inflam mation induced by cationic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The test method used was as described previously [12]. Briefly, male MF 1 mice, weighing approximately 20 g, were treated with cyclophosphamide (250 mg.kg -1, i.p.)…”
Section: Mbsa Delayed Hypersensitivity Testmentioning
confidence: 99%